Honen's senchakushu : (University of Haiwai'i Press, 1998)
Honen Bo Genku (1133-1212), or simply Honen, is one of the most outstanding figures in the long history of Japanese Buddhism. Along with Dogen, Nichiren, and Shinran, his disciple, he represents the core of the revolutionary Kamakura Buddhist movement that created the first popular and uniquely Japanese forms of Buddhism. Though not as well known in the West as his counterparts, Honen is perhaps the most pivotal of the four because he was the first to break with the established centers of Tendai and Shingon, those Buddhist sects patronized by the royal court and military authorities. This volume is the culmination of an eight-year project of the Taisho University Center for Comprehensive Buddhist Studies led by Professor Hirokawa Takatoshi. The project has sought to present a translation of Honen's seminal work, the Senchakushu, previously unavailable in a complete English text. The Senchakushu was compiled over a period of intense devotion to Amida Buddha. In the style of scholarship prevalent during this period, Honen presents this spiritual vision through adapted textual passages from the Pure Land tradition. This vision would seem to reflect a rather simplistic and single-minded devotion to the practice of nembutsu.Yet the insightful analysis presented in a lengthy Introduction that precedes the translation shows that while Honen's teaching offers a simple and accessible practice to the ordinary person it is also a finely tuned and deeply thought-out vision of spiritual transformation. In addition to offering an important foundation for guiding the reader through the translation, the Introduction also presents a lively and detailed portrait of Honen and his times.